Change of the shape of mass and charge distributions in fission of Cf isotopes with excitation energy; Physical Review C; Vol. 99, iss. 6 - Pasca H. Horia; Andreev A. V. Aleksandr Vasiljevich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2019, 2019)
Title screen